Hog Feeders? - Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1988)
During the past 6 yr, extensive research has been conducted at KSU to evaluate feeding systems and various types of wet and dry feeders. Comparisons have been made between timed-feeding and ad libitum feeding systems using dry or wet feeders. Timed-feeding did not improve pig performance (ADG, F/G) when compared with ad libitum dry feeding. Wet feeding in most of the trials resulted in approximately 5% improvement in both average daily gain and feed efficiency. Feeding hogs with an oval or rectangular dry feeder resulted in similar pig performance. A11 feeders were easily adjusted to reduce feed wastage to a minimum.; Swine Day, Manhattan, KS, November 17, 1988
Keywords: Swine day; 1988; Kansas Agricultural Experiment Station contribution; no. 88-149-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 556; Swine; Swine technology; Feeding systems; Dry or wet feeders